Public Investment, Revenue Shocks, and Borrowing Restrictions - Thiess Büttner; David E. Wildasin (Verein für Socialpolitik, 2010)
This paper lays out a theory of taxation and public investment in an intertemporal setting under conditions of revenue shocks. Without borrowing restrictions, the optimal policy is characterized by smooth time paths of taxes and public investment. While the introduction of formal borrowing restrictions leads to some precautionary savings, it gives rise to fluctuations in public investment in response to adverse but also favorable revenue shocks. This theoretical result is tested empirically using data on public investment of more than 1,000 US municipalities in the period from 1972 to 1997 in various states that impose or do not impose borrowing restrictions on municipalities. The empirical results are supportive, indicating that in presence of borrowing restrictions public investment is becoming responsive to the deficit and is stronger affected by revenue shocks.
Keywords: H74; H72; H71; 330